Cystic fibrosis transmembrane conductance regulator (CFTR)-targeted therapeutics for cystic fibrosis - Veselu, D-F; Yeh, H-I; Rodrat, M; Bradbury, JD; Manzanares Fornies, Y; Li, H; Shoemark, DK; Oliveira, ASF; Hwang, T-C; Sheppard, DN (Springer, 2024)
Treatment of the common life-limiting genetic disease cystic fibrosis (CF) has been transformed by small molecule therapeutics that target the root cause of the disease, pathogenic variants in the ATP-binding cassette transporter cystic fibrosis transmembrane conductance regulator (CFTR). Here, we selectively review understanding of CFTR function as an ATP-gated anion channel, its physiological role in epithelia and the molecular mechanisms of CFTR dysfunction, which paved the way for the development of CFTR modulators. These orally bioavailable small molecules include CFTR correctors, which improve CFTR folding and domain assembly to facilitate its transport to the plasma membrane and CFTR potentiators, which enhance channel gating to augment CFTR function. Elexacaftor-tezacaftor-ivacaftor, the combination of two CFTR correctors and one CFTR potentiator, is a highly effective therapeutic for most, but not all, people with CF. Ongoing research aims to provide highly effective therapeutics for all people with CF and ultimately cure the disease.